Current knowledge and future prospects of vaccines against cyprinid herpesvirus 3 (CyHV-3). Issue 93 (October 2019) - Boutier, Maxime; Gao, Yuan; Donohoe, Owen; Vanderplasschen, Alain
Abstract: Aquaculture is one of the world's most important and fastest growing food production sectors, with an average annual growth of 5.8% during the period 2001–2016. Common carp ( Cyprinus carpio ) is one of the main aquatic species produced for human consumption and is the world's third most produced finfish. Koi carp, on the other hand, are grown as a popular ornamental fish. In the late 1990s, both of these sectors were threatened by the emergence of a deadly disease caused by cyprinid herpesvirus 3 (CyHV-3; initially called koi herpesvirus or KHV). Since then, several research groups have focused their work on developing methods to fight this disease. Despite increasing knowledge about the pathobiology of this virus, there are currently no efficient and cost-effective therapeutic methods available to fight this disease. Facing the lack of efficient treatments, safe and efficacious prophylactic methods such as the use of vaccines represent the most promising approach to the control of this virus. The common carp production sector is not a heavily industrialized production sector and the fish produced have low individual value. Therefore, development of vaccine methods adapted to mass vaccination are more suitable. Multiple vaccine candidates against CyHV-3 have been developed and studied, including DNA, bacterial vector, inactivated, conventional attenuated and recombinant attenuated vaccines. However, there is currently only one vaccine commercially available in limited regions. The present review aims to summarize and evaluate the knowledge acquired from the study of these vaccines against CyHV-3 and provide discussion on future prospects. Highlights: Aquaculture is one of the world's fastest growing food production sectors. Common carp ( Cyprinus carpio ) is currently the world's 3rd most produced finfish. Cyprinid herpesvirus 3 (CyHV-3) is a lethal pathogen of common carp. CyHV-3 disease is stimulating the development of safe and efficacious vaccines.